Gender Stereotype and Distribution of Masculinity Discourse in Novel Balada Si Roy; Joe By Gola Gong - Mahendra, Ilham (ALAYASASTRA, 2017)
This paper is based on the readings of typical male issues raised in novel Balada Si Roy: Joe as a reflection and representation of masculine narratives. The purpose of this paper is to reveal the reflection of gender stereotypes, especially masculine, and the spread of masculinity discourse. This paper use sociological approach, focusing on the use of theories of gender stereotypes (good or bad man) and masculinity (how to be a man). The results obtained that the author offers a coherence of male image through his work, to provide fantasies for the process of gender actualization. In other words, the author is a representation of a socio-cultural-socialization- of how to become a man. It is reflected by Roy's character as a good man icon, because it reflects how to be man. Thus, the novel BSR:J is an agent that reproduces the masculine image in order to preserve and spread dominant groups narratives, in this case patriarchal.